2016
DOI: 10.1002/2016jg003343
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivity of soil microbial communities: An application of macromolecular rate theory to microbial respiration

Abstract: There is compelling evidence that microbial communities vary widely in their temperature sensitivity and may adapt to warming through time. To date, this sensitivity has been largely characterized using a range of models relying on versions of the Arrhenius equation, which predicts an exponential increase in reaction rate with temperature. However, there is growing evidence from laboratory and field studies that observe nonmonotonic responses of reaction rates to variation in temperature, indicating that Arrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 50 publications
(70 reference statements)
1
49
0
Order By: Relevance
“…In a previous study (Alster et al, 2016), we found that temperature sensitivity varied among soil microbial communities. We applied both Arrhenius and MMRT to our data to compare the effectiveness of each of these models and demonstrate how Arrhenius estimates of temperature sensitivity may not be sufficient, even within in situ representative temperature ranges.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In a previous study (Alster et al, 2016), we found that temperature sensitivity varied among soil microbial communities. We applied both Arrhenius and MMRT to our data to compare the effectiveness of each of these models and demonstrate how Arrhenius estimates of temperature sensitivity may not be sufficient, even within in situ representative temperature ranges.…”
Section: Introductionmentioning
confidence: 63%
“…In order to quantitatively characterize temperature responses of each of the 21 isolate × enzyme combinations, we plotted the natural log of the reaction rate against temperature and fitted both the Arrhenius and MMRT equations using an analytic Gauss-Newton for Arrhenius and a numerical Gauss-Newton for MMRT in JMP Pro 11 (Schipper et al, 2014; Alster et al, 2016). Parameters E A and ΔCp, along with their uncertainty, were reported by the software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we (Alster, Baas, Wallenstein, Johnson, & Fischer, ) introduced a mechanism for characterizing temperature sensitivity as a microbial trait. We found that temperature sensitivity can be characterized as a microbial trait itself with distinct temperature sensitivity trait values, influenced by genetic and environmental variation (Alster, Baas, et al, ; Alster, Koyama, Johnson, Wallenstein, & Fischer, ). Defining temperature sensitivity as a microbial trait with measurable and intercomparable characteristics adds another technique to predict microbial community assemblage and creates an important tool to evaluate microbial response to climate change and impact on ecosystem function.…”
Section: Introductionmentioning
confidence: 99%
“…At warm sites, microbial enzyme activity was closer to the predicted maximum activity based on the heat capacity of enzymes (Figure S3). As a result, the model variants predicted smaller SOC stock losses with warming because the increased encounter rate between molecules when warmed (Davidson et al, ; Rodrigo et al, ) was compensated by the decreased ability of proteins (such as enzymes) to bind substrates at high temperatures (Alster et al, ; Ratkowsky et al, ; Schipper et al, ).…”
Section: Discussionmentioning
confidence: 99%